2019
DOI: 10.26656/fr.2017.4(2).323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of banana peel extract on storage stability of banana cv. Sagar

Abstract: Due to shorter shelf life and inadequate postharvest facilities, every year a huge loss of banana occurs in Bangladesh. An effective postharvest practice can reduce the spoilage rate as well as can extend the shelf life of banana. In this context, this current study was conducted to assess the effect of banana peel extract (BPE) on shelf life and quality characteristics of ripe banana (cultivar: sagar). Four types of ripe banana samples were prepared and were assessed to find the changes of different physico-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
(20 reference statements)
2
15
0
Order By: Relevance
“…During ripening, the starch and other insoluble carbohydrates get hydrolysed by hydrolytic enzymes into soluble sugars which is responsible for the increase in the total soluble solids (Beckles, 2012). The results obtained in present studies for total soluble sugars are in accordance with the previous reports published on tomato (Devi et al ., 2019; Steelheart et al ., 2019), banana (Rahman et al ., 2020) and peach (Abdipour et al ., 2019). Results showed that the pretreatment of SA could significantly retard the increase of total soluble solids as compared to control fruit.…”
Section: Discussionmentioning
confidence: 99%
“…During ripening, the starch and other insoluble carbohydrates get hydrolysed by hydrolytic enzymes into soluble sugars which is responsible for the increase in the total soluble solids (Beckles, 2012). The results obtained in present studies for total soluble sugars are in accordance with the previous reports published on tomato (Devi et al ., 2019; Steelheart et al ., 2019), banana (Rahman et al ., 2020) and peach (Abdipour et al ., 2019). Results showed that the pretreatment of SA could significantly retard the increase of total soluble solids as compared to control fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds were then dried in a vacuum dryer at 55 o C for 6 hr and grinded by a grinder (Yeasmen and Islam, 2015). Fifty (50) g of pumpkin seed powder was mixed with 500 ml of 96% ethanol followed by magnetic stirring at 900 rpm 30 min and sonicated at 45 o C for 55 min to increase the efficiency of extraction (Bisht et al, 2016;Rahman et al, 2019). Three (3) stage extractions were used for the extraction of PSE i.e.…”
Section: Preparation Of Pumpkin Seed Extractsmentioning
confidence: 99%
“…Alcoholic flavor was removed from the PSE passing through nitrogen gas. Extracted PSE was kept at 4 o C for further processing (Bisht et al, 2016;Rahman et al, 2019).…”
Section: Preparation Of Pumpkin Seed Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Oyeyinka and Afolayan (2020), bananas are known to offer numerous health benefits as its edible portion contains carbohydrates and fibre that act as long-lasting form of fuel and helps to stabilize blood sugar levels. Also, it contains vitamins C, A and B complexes, among other nutrients and it is a good source of potassium and magnesium; relevant to maintain nerve and muscle function, in addition to maintaining pH and fluid balance (Rahman et al, 2019;Oyeyinka and Afolayan, 2020).…”
Section: Introductionmentioning
confidence: 99%